2021
DOI: 10.1002/fsn3.2139
|View full text |Cite
|
Sign up to set email alerts
|

Development of camel and cow's milk, low‐fat frozen yoghurt incorporated with Qodume Shahri (Lepidium perfoliatum) and cress seeds (Lepidium sativum) gum: Flow behavior, textural, and sensory attributes' assessment

Abstract: In this study, the effect of different concentrations (0.2%, 0.1%, and 0%) of some plant seed gums (Qodume Shahri (Lepidium perfoliatum) and cress (Lepidium sativum)) as the stabilizer on the flow behavior, textural, and sensory properties of frozen yoghurt produced from camel and cow's milk was investigated. The results showed that plant seed gums significantly affected the viscosity, overrun and melting rate, textural, and sensory properties of frozen yoghurt samples prepared from camel and cow's milk. Also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…The viscosity and K values of ice cream samples were different from those reported by Azari‐Anpar et al. (2021), who found that the viscosity and K values of ice cream samples from camel's milk containing Qodume Shahri and cress seed gum increased compared to the control sample. Karaman and Kayacier (2012) found that K values of ice cream samples enriched with herbal tea were lower than the control sample.…”
Section: Resultscontrasting
confidence: 87%
See 2 more Smart Citations
“…The viscosity and K values of ice cream samples were different from those reported by Azari‐Anpar et al. (2021), who found that the viscosity and K values of ice cream samples from camel's milk containing Qodume Shahri and cress seed gum increased compared to the control sample. Karaman and Kayacier (2012) found that K values of ice cream samples enriched with herbal tea were lower than the control sample.…”
Section: Resultscontrasting
confidence: 87%
“…(2017) and Azari‐Anpar et al. (2021). It has been explained that the overrun values were affected by fat globule and protein/emulsifier content (Kurultay et al., 2010) and the production system (Salem et al., 2017).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…This phenomenon demonstrates that BSGPs resulted in the yogurt having increased gel formation, which could be beneficial for the textural properties as well as for the consistency and for reducing syneresis. Different shear stress trends in yogurt have been reported previously and were found to be dependent on the ingredients that had been added as well as the treatments ( Azari-Anpar et al, 2021 ; Körzendörfer et al, 2019 ; Vénica et al, 2020 ), which were shown to be related to flow behavior-related properties, microstructural properties, and syneresis.…”
Section: Resultsmentioning
confidence: 55%
“…The power law model, Herschel-Bulkley model, and Casson model were used to calculate the consistency index (k), the flow behavior index (n), yield stress (τ 0 ), and correlation coefficient (R 2 ) of samples. Finally, the experimental data were fitted according to these three models (Azari-Anpar et al, 2021).…”
Section: Rheological Testsmentioning
confidence: 99%